A contribution to knowledge of the aetiology and indirect impact of inflammatory bowel diseases: (based upon analysis of routinely and semi-routinely available data) - Card, Timothy R. (2004)
The incidence of the idiopathic inflammatory bowel diseases ulcerative colitis and Crohn’s disease appears to have risen markedly during the 20th century. These diseases now account for a considerable proportion of the workload of gastroenterologists in the developed world, and may affect as much as 1% of the population at some point in their lives.